2015
DOI: 10.1002/pssc.201510019
|View full text |Cite
|
Sign up to set email alerts
|

CVD synthesis and catalytic combustion application of chromium oxide films

Abstract: Chromiumoxide (Cr2O3) thin films were controllably synthesized by pulsed‐spray evaporation chemical vapor deposition (PSE‐CVD) for deep oxidation of propene. The effect of substrate temperature on the growth kinetics and morphology of the films was investigated. The prepared samples were comprehensively characterized with respect to structure, morphology and surface composition with XRD, SEM and XPS, respectively. An in situ diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS) was involved to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Therefore, numerous investigations on the development of TMOs catalysts are mainly focused on this type of oxides. Several n-type and p-type single oxides such as Co 3 [46] have been prepared via PSE-CVD and successfully tested as active catalysts toward total oxidation of some real fuels such as CO, C 2 H 2 , C 3 H 6 , n-C 4 H 8 and C 2 H 6 O as representatives of industrial exhaust stream or VOCs. Among these oxides mentioned above, a few of them seem to be particularly promising.…”
Section: Tailored Synthesis Characterization and Application Of Singmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, numerous investigations on the development of TMOs catalysts are mainly focused on this type of oxides. Several n-type and p-type single oxides such as Co 3 [46] have been prepared via PSE-CVD and successfully tested as active catalysts toward total oxidation of some real fuels such as CO, C 2 H 2 , C 3 H 6 , n-C 4 H 8 and C 2 H 6 O as representatives of industrial exhaust stream or VOCs. Among these oxides mentioned above, a few of them seem to be particularly promising.…”
Section: Tailored Synthesis Characterization and Application Of Singmentioning
confidence: 99%
“…In addition to its good thermal stability, Cr 2 O 3 exhibited attractive performance in the low-temperature abatement of VOCs. Recently, Liang et al [46] reported the synthesis of Cr 2 O 3 by PSE-CVD for the total oxidation of propene. (Figure 8b) were formed in the reaction without catalyst, which could originate from the partial oxidation reaction.…”
Section: Chromium Oxidementioning
confidence: 99%
See 2 more Smart Citations